Law of The Productive Testicles - Frengki Hardian (CV. Publikasi Indonesia, 2024)
The role of zakat as ijtima'iyah Aaliyah worship in Islam focuses on two main functions of zakat, namely cleansing property and souls and being a community fund to reduce poverty. Zakat mal and zakat fitrah were discussed, with emphasis on the need for a productive zakat approach as a long-term solution. The research aims to understand the concept of productive zakat from the perspective of Yusuf Al-Qardhawi and Imam Nawawi, including an understanding of the main purpose of productive zakat in alleviating poverty and improving mustahik welfare. This research uses a documentary-descriptive approach method with literature study, where written data is analyzed based on context. The results showed that the distribution of productive zakat according to Yusuf Al-Qardhawi played an important role in developing the mustahiq economy. The majority of scholars support the concept of productive zakat as a strategy to improve the economic life of Mustahiq. The conclusion of this study underscores the urgency of productive zakat in the context of Islamic teachings and the welfare of the Ummah. The empowerment of Mustahiq through training and skill development is the main focus to increase the effectiveness of productive zakat. Although there is no specific reference in the Qur'an or hadith regarding productive zakat, the allocation of zakat clearly stated in surah At-Tawbah verse 60 provides a basis for the distribution of zakat that supports the economic improvement of Muslims.